1972
DOI: 10.1007/bf01867845
|View full text |Cite
|
Sign up to set email alerts
|

The molecular composition of some lipid bilayer membranes in aqueous solution

Abstract: Summary. An analytical technique is described for direct determination of the molecular composition of lipid bilayer membranes in aqueous solution. Membranes formed from chemically pure, radioactively labeled components, were sampled by pipetting a mercury droplet through the bilayer-water interface. During this procedure, the membrane remains intact but decreases in area with a concomitant increase in the area of the surrounding bulk phase. It is shown that each mercury droplet is covered with a fragment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Furthermore, the fluidity of the black lipid membrane may be significantly influenced by the presence of solvent, e.g. decane, in the film [17]. For the black lipid membrane system with membranes of phosphatidylinositol isolated from brain, and a mixture of soybean phospholipids, turnover constants of about 104 [11,13] and and 5 • 10 3 [15] ions/molecule valinomycin per s were obtained respectively at 25 '>C. On the other hand, we find for egg phosphatidylcholine liposomes at 30 ~'C a value of about 328 ions/molecule valinomycin per s (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fluidity of the black lipid membrane may be significantly influenced by the presence of solvent, e.g. decane, in the film [17]. For the black lipid membrane system with membranes of phosphatidylinositol isolated from brain, and a mixture of soybean phospholipids, turnover constants of about 104 [11,13] and and 5 • 10 3 [15] ions/molecule valinomycin per s were obtained respectively at 25 '>C. On the other hand, we find for egg phosphatidylcholine liposomes at 30 ~'C a value of about 328 ions/molecule valinomycin per s (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…One of the drawbacks of the black lipid membrane system, especially in studying the effect of variation in the fatty acid composition on the valinomycin-mediated cation transport, is the presence of considerable amounts of solvent in the bilayer structure [17]. Another disadvantage is that such experiments require extended time periods, leading to the uncertainty of adsorption of valinomycin at the walls of the lest cells, as discussed in the accompanying paper [18].…”
Section: Introductionmentioning
confidence: 99%
“…If the amount of solvent estimated by Pagano et al (1972) is taken as an indication of the volume of trapped lenses, and a lens diameter of the order of 1 [Lm is assumed, the area reduction can be considerable. Thus a significant variation with time of the specific capacitance as the lenses coalesce and diffuse to the border would be expected.…”
Section: Validity Of Measured Specific Capacitancementioning
confidence: 99%
“…It is inevitable that there is residual decane left in the central bilayer portion of the membrane. Past estimation of the volume ratio of n-decane versus PC was 0.35-0.45 after the thinning of the bilayer 18,[20][21][22] . EM examination of the thinned bilayer showed that there were lenses of decane sandwiched between the two leaflets of a bilayer 22 .…”
Section: Electrical Recordings From Kvap Channels In Lipid Bilayersmentioning
confidence: 99%